DLX3 Inhibits the Proliferation of Human Dental Pulp Cells Through Inactivation of Canonical Wnt/β-Catenin Signaling Pathway - Zhan, Yunyan; Li, Xiaoyan; Gou, Xiaohui; Yuan, Guohua; Fan, Mingwen; Yang, Guobin (Frontiers in Physiology, 2018)
Homeodomain gene Distal-less-3 (Dlx3) plays an important role during tooth development. Our previous studies indicate that DLX3 inhibits proliferation of human dental pulp cells (hDPCs). However, the mechanism of DLX3 regulating proliferation of hDPCs and maintaining the quiescence of the cells remain unknown. Given the importance of canonical Wnt signaling in odontoblast proliferation and tooth development, we hypothesized that DLX3 inhibited proliferation of hDPCs through inactivation of canonical Wnt signaling. We found overexpression of DLX3 in primary hDPCs by infection of recombinant lentivirus resulted in downregulation of canonical Wnt signaling and its downstream target genes. And when these cells were treated with lithium chloride, the proliferation inhibition by DLX3 was reversed. We also found that DLX3 enhanced the expression of DKK1 and the reduced proliferation of hDPCs by DLX3 was reversed with knock-down of DKK1. Furthermore, luciferase reporter assay and chromatin immunoprecipitation assay showed DLX3 was able to bind to Dkk1 promoter region from nucleotides (nt) -1656 to -1245, and stimulated Dkk1 promoter activity. Mutagenesis studies further revealed two DLX3 responsive elements in Dkk1 promoter. Taken together, our data indicate that DLX3 inhibits proliferation of hDPCs via inactivation of Wnt/β-catenin signaling pathway by directly binding to Dkk1 promoter and increasing its expression.